Mosaic RBD Nanoparticles Elicit Protective Immunity Against Multiple Human Coronaviruses in Animal Models - Yanjun Zhang; Jing Sun; Jian Zheng; Suxiang Li; Haiyue Rao; Jun Dai; Zhaoyong Zhang; Yanqun Wang; Donglan Liu; Zhao Chen; Wei Ran; Airu Zhu; et al. (Advanced Science, 2024)
Abstract To combat SARS‐CoV‐2 variants and MERS‐CoV, as well as the potential re‐emergence of SARS‐CoV and spillovers of sarbecoviruses, which pose a significant threat to global public health, vaccines that can confer broad‐spectrum protection against betacoronaviruses (β‐CoVs) are urgently needed. A mosaic ferritin nanoparticle vaccine is developed that co‐displays the spike receptor‐binding domains of SARS‐CoV, MERS‐CoV, and SARS‐CoV‐2 Wild‐type (WT) strain and evaluated its immunogenicity and protective efficacy in mice and nonhuman primates. A low dose of 10 µg administered at a 21‐day interval induced a Th1‐biased immune response in mice and elicited robust cross‐reactive neutralizing antibody responses against a variety of β‐CoVs, including a series of SARS‐CoV‐2 variants. It is also able to effectively protect against challenges of SARS‐CoV, MERS‐CoV, and SARS‐CoV‐2 variants in not only young mice but also the more vulnerable mice through induction of long‐lived immunity. Together, these results suggest that this mosaic 3‐RBD nanoparticle has the potential to be developed as a pan‐β‐CoV vaccine.